2020
DOI: 10.1177/0145482x20901380
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Vocational Rehabilitation Data about People with Visual Impairments: Demographics, Services, and Long-Run Labor Market Trends

Abstract: Introduction: This study describes the characteristics of, services received by, and labor market outcomes of applicants with visual impairments to three state vocational rehabilitation programs. Our objective is to both document cross-state variation in vocational rehabilitation clientele and services and provide new insights on the longitudinal labor market outcomes of clients with visual impairments (i.e., blindness or low vision). This analysis is a first step in assessing the returns to vocational rehabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Twelve studies (21%) used a definition that included competitive employment, 23,49,54–63 five used paid or gainful employment 19,64–67 and one study used open employment 68 or earnings set above minimum federal wage 69 . Although most studies focused on describing employment outcomes for working‐age adults, a few (12%) also included participants who were not part of the working‐age population (e.g., retired, students) or lacked a separate analysis for working‐age participants 54,70–75 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies (21%) used a definition that included competitive employment, 23,49,54–63 five used paid or gainful employment 19,64–67 and one study used open employment 68 or earnings set above minimum federal wage 69 . Although most studies focused on describing employment outcomes for working‐age adults, a few (12%) also included participants who were not part of the working‐age population (e.g., retired, students) or lacked a separate analysis for working‐age participants 54,70–75 …”
Section: Resultsmentioning
confidence: 99%
“…69 Although most studies focused on describing employment outcomes for working-age adults, a few (12%) also included participants who were not part of the working-age population (e.g., retired, students) or lacked a separate analysis for working-age participants. 54,[70][71][72][73][74][75] Most studies included samples with all participants being visually impaired, except for 10 studies (18%), 27,70,[72][73][74][76][77][78][79][80] of which half was part of a national epidemiological study. 27,70,72,73,80 The severity of visual impairment (e.g., total/legal blindness, low vision) or fulfilment of certain criteria for low vision (e.g., the criteria for visual impairment by the International Classification of Diseases [ICD] or the WHO) was reported in the majority of studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…N = 1555. Purposive sampling Novel, multivariate model Results showed that when combining the employment and earnings effects together, apart from diagnosis and evaluation, all service types had positive long-run effects Clapp et al 87 VR administrative data from three separate states; N = 1964 Descriptive analysis Results indicated persistent earnings benefits; however, there was substantial cross-state heterogeneity relative to types of services offered. Recommendations relative to care practitioners aiding people with BVI in cultivating independence and seeking alternative quality of life outcomes McDonnall & Lund, 88 Hiring managers.…”
Section: Methodsmentioning
confidence: 99%
“…Research with other data sources has focused on earnings and factors associated with earnings of Americans with visual impairments (Bell & Mino, 2015; Silverman et al, 2019), including vocational rehabilitation consumers (Bell, 2010; Capella, 2001; Clapp et al, 2020; Estrada-Hernández, 2008; Giesen & Lang, 2018). The average annual earnings of survey participants with visual impairments in 2011 were $40,134, and median earnings were $35,000 (Bell & Mino, 2015).…”
mentioning
confidence: 99%